Cave crickets and cave weta (orthoptera, rhaphidophoridae) from the southern end of the world: a molecular phylogeny test of biogeographical hypotheses - Giuliana Allegrucci; Gianmaria Carchini; Valerio Sbordoni; Steve A. Trewick; Angela Fortunato (Journal of Orthoptera Research, 2010)
Abstract In this study we reconstructed the molecular phylogeny and attempted to infer historical biogeography of a sample of cricket species, most of them cave-dwelling, belonging to the subfamily Macropathinae (Orthoptera, Rhaphidophoridae) which shows a clear Gondwanan distribution. We sequenced fragments of 4 genes (12S rRNA, 16S rRNA, 18S rRNA and 28S rRNA), for a total of 1993 bp. We present here preliminary data based on a total of 17 species, 11 belonging to Macropathinae and representative of the main regions of Gondawanaland, 7 to Aemodogryllinae and Rhaphidophorinae from India, Bhutan, China, Philippines and the Sulawesi Islands. The use of relaxed molecular clocks by means of Bayesian analysis allowed us to estimate the timing of the main cladogenetic events, using calibration of a molecular clock; the clock is based on the plate disjunction of Africa from South America, Australia from Zealandia (New Zealand), or Australia from Antarctica. The latter was considered at two different datings on .